Double inferior alveolar nerve canals and mental foramina in the mandible : a computed tomography study at a private dental clinic in Kenya - Marnewick, J.C. (Johan) (University of Pretoria, 2018)
Dissertation (MSc Dentistry)--University of Pretoria, 2017.